Investigation of an outbreak of metallo-β-lactamase producing Pseudomonas aeruginosa linked to the water distribution system in a Hematopoietic Stem Cell Transplantation Unit - Daniela Santonato; Ivana Martinelli; Alejandra Quevedo; Roxana Sadorin; Andrea Novau; Leonardo Fabbro; María de los Ángeles Cuello Mena; Vanessa Araoz Sanchez; Wanda Cornistein (Cambridge University Press, 2024)
Abstract Introduction: Pseudomonas aeruginosa (PA) is an opportunistic pathogen. Metallo-β-lactamase producing PA (MBL-PA) poses a problematic issue given limited available treatments. In Argentina, it accounts for less than one percent of healthcare-associated infections. Objectives: To describe an outbreak of verona integron-encoded metallo-β-lactamase (VIM) Pseudomonas aeruginosa in a Hematopoietic Stem Cell Transplantation Unit (HSCTU), and the strategies implemented to control it. Materials and methods: Investigation of an outbreak by MBL-PA in an HSCTU in May 2023. Active case search, environmental sampling, identification and susceptibility pattern of strains, mitigation strategies. Case: patient admitted to the HSCTU with positive sample for MBL-PA after 48 hours of admission. Mitigation strategies: biweekly rectal swabbing, contact precautions, dedicated nursing staff, waterless patient care, and disinfection of bacterial reservoirs. Results: In May 2023 two cases were identified. A retrospective search determined an additional case. One (10%) of the environmental samples was positive for VIM type MBL-PA in the drain of the hand hygiene station in the nurse's office. Strains were susceptible to colistin and fosfomycin and intermediate to aztreonam. Incidence density (ID) of colonization and infection by MBL-PA in the HSCTU were .68/1,000 patient-days (pd) and 0, respectively, in the second semester of 2022. In the first semester of 2023, ID rose to 2.93/1,000 pd for colonization and .73/1,000 pd for infection. Mitigation strategies aimed at reducing exposure of immunocompromised hosts to water. No new cases have been identified since. Conclusions: We report an MBL-PA outbreak probably linked to the water distribution system in an HSCTU, and mitigation strategies put in place.